Influence of noncondensible gas on flowing characteristics of multiple nozzle oil jet pump for lubrication system in steam turbine. (December 2015) - Zhang, Jun; Mao, Jing-ru; Wang, Shun-sen; Zhang, Jun-jie; Sun, Peng
The full cavitation model introduced by Singhal et al. was partly improved based on experimental results. The improved cavitation model is used to simulate cavitating flow in multiple nozzle oil jet pump for lubrication system in steam turbine. The influence of noncondensible gas on flowing characteristics of multiple nozzle oil jet pump was studied with noncondensible gas content in the range of 0.01–500 ppm. Results show that noncondensible gas has little influence on nonchoking flow while imminent choking flow and deep choking flow are greatly affected. With the increase of noncondensible gas, multiple nozzle oil jet pump enters choking flow earlier. The maximum suction flow rate per unit throat area of multiple nozzle oil jet pump remains constant with varying pressure ratios and area ratios under choking flow, which is only determined by the noncondensible gas content. It is suggested that the maximum suction flow rate per unit throat area is used for the prediction of choking flow in multiple nozzle oil jet pump. This study also provides qualitative criteria for the upper limit of water content in lubrication oil, which avoids multiple nozzle oil jet pump working under choking flow.